2007
DOI: 10.1097/bpo.0b013e3180342ff5
|View full text |Cite
|
Sign up to set email alerts
|

Unique Case of Polydactyly and A New Classification System

Abstract: Polydactyly of the hands or feet is a common birth deformity. We recently encountered a female infant with a case of a crossed type 1 polydactyly with a mixed polydactyly of the feet. A mixed and crossed polydactyly is a rare finding with only one other reported case. This is the first report of crossed and mixed polydactyly of the feet presenting with 7 complete toes on each foot without syndactyly. In addition to a discussion of the treatment, this case has lead us to propose a more complete and less confusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…This pedigree showed AD with incomplete penetrance which means that the individual who inherits the mutation will not necessary presented with the trait as in this Egyptian family there were members with apparently normal digits. This is in accordance with (Haber et al, 2007 andScott-Emuakpor andMadueke, 1976) who reported that postaxial polydactyly showed autosomal dominant inheritance with decreased penetrance (64.9%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This pedigree showed AD with incomplete penetrance which means that the individual who inherits the mutation will not necessary presented with the trait as in this Egyptian family there were members with apparently normal digits. This is in accordance with (Haber et al, 2007 andScott-Emuakpor andMadueke, 1976) who reported that postaxial polydactyly showed autosomal dominant inheritance with decreased penetrance (64.9%).…”
Section: Discussionsupporting
confidence: 91%
“…Polydactyly is presented in different patterns (Watson and Hennrikus, 1997). According to anatomical position of the extra digit, polydactyly may be preaxial (radial or tibial), postaxial (ulnar or fibular) or central polydactyly (presence of duplicated second, third, or fourth digits) (Haber et al, 2007). Crossed polydactyly is defined as presence of preaxial polydactyly of hands and postaxial of feet, or the reverse (Hosalkar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Another unusual form of polydactyly proposed by Nathan and Keniston is that of mixed polydactyly where preaxial and postaxial polydactyly exist in the same extremity. [6,7] Polydactyly may occur F: female; M: male.…”
Section: Discussionmentioning
confidence: 99%
“…In the modifi ed classifi cation, [6] type A polydactyly would be preaxial or postaxial, and could be unilateral or bilateral in hands or feet. Type B would indicate the polydactyly of the upper and lower extremities, either preaxial or postaxial.…”
Section: Familial Crossed Polysyndactylymentioning
confidence: 99%
“…3,6 The PAP involves extra digit at fifth digit/ toe and the least common type, axial (central) polydactyly characterized by duplication of central three digits (second, third or the fourth) and PPD involves a supernumerary digit/toe affecting the first digits/ toe (thumb). 7,8 In addition, other complex types of polydactylies like palmar/ventral and dorsal type polydactyly, haas-type polysyndactyly and mirror image polydactyly (MIP) have been reported in the literature. 3,9 The PAP is classified into two broad categories type A and B.…”
Section: Introductionmentioning
confidence: 99%